The left main bronchus transected incorrectly during video-assisted thoracoscopic lobectomy: a case report - Yuma Shindo; Masahiro Miyajima; Yasuyuki Nakamura; Wataru Arai; Ryunosuke Maki; Kodai Tsuruta; Atsushi Watanabe (Surgical Case Reports)
Abstract Background Several severe intraoperative complications of lung cancer surgery have been reported, but the incorrect transection of the main bronchus is a very rare and serious complication. We report a surgical case of a patient with left lower lobe lung cancer invading the inferior segment of the lingula, with fused interlobar fissure and dense pleural adhesion, in which the left main bronchus was mistaken for the left lower lobe bronchus and was transected. Case presentation A 64-year-old woman with lung adenocarcinoma was referred to our hospital for surgical treatment. Chest computed tomography (CT) scan showed a 30-mm nodule with a clear border and irregular margins in the center of the anterior (S8) segment of the lower lobe of the left lung and another similar 30-mm nodule in the lateral (S9) segment of the same lobe. Metastasis within the same lobe was suspected. A thoracoscopic left lower lobectomy was scheduled for the patient. As the patient had a moderately, fused fissure, dense pleural adhesion, and suspicious tumor invasion from the left S8 segment to the left S5 segment, and the interlobar node tightly adhered to the main PA at the site of basilar artery origin of the LLL, we performed left lower lobectomy and a left S5 segmentectomy using the fissureless fissure-last technique. During surgery, the left main bronchus was mistaken for the left lower lobe bronchus and was transected. After transecting the left main bronchus, we performed a sleeve bronchoplasty to prevent pneumonectomy. Conclusions We experienced the rare and serious intraoperative complication of the incorrect transection of the main bronchus. There are few reports of this intraoperative complication, and it should not be overlooked by surgeons.